Class Switch Recombination Efficiency and Junction Microhomology Patterns in Msh2-, Mlh1-, and Exo1-Deficient Mice Depend on the Presence of μ Switch Region Tandem Repeats() - Eccleston, Jennifer (2009)
The Msh2 mismatch repair (MMR) protein is critical for class switch recombination (CSR) events that occur in mice that lack the Sμ tandem repeat (SμTR) region (SμTR(−/−) mice). The pattern of microhomology among switch junction sites in Msh2-deficient mice is also dependent on the presence or absence of SμTR sequences. It is not known whether these CSR effects reflect an individual function of Msh2 or the function of Msh2 within the MMR machinery. In the absence of the SμTR sequences, Msh2 deficiency nearly ablates CSR. We now show that Mlh1 or Exo1 deficiencies also eliminate CSR in the absence of the SμTR. Furthermore, in SμTR(−/−) mice, deficiencies of Mlh1 or Exo1 result in increased switch junction microhomology as has also been seen with Msh2 deficiency. These results are consistent with a CSR model in which the MMR machinery is important in processing DNA nicks to produce double-stranded breaks, particularly in sequences where nicks are infrequent. We propose that double-stranded break paucity in MMR-deficient mice leads to increased use of an alternative joining pathway where microhomologies are important for CSR break ligation. Interestingly, when the SμTR region is present, deficiency of Msh2 does not lead to the increased microhomology seen with Mlh1 or Exo1 deficiencies, suggesting that Msh2 might have an additional function in CSR. It is also possible that the inability to initiate MMR in the absence of Msh2 results in CSR junctions with less microhomology than joinings that occur when MMR is initiated but then proceeds abnormally due to Mlh1 or Exo1 deficiencies.